AL-QARDH AL-HASAN: SOFT AND BENEVOLENT LOAN PADA BANK ISLAM - Ismail Hannanong; Aris Aris (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
Akad Al-Qardh is an agreement or agreement between the two parties, whereby the first party provides assets or provides property in the sense of lending to a second party as a borrower of money or a person who receives assets that can be billed or reimbursed, in other words lend property to other people who need fast funds without expecting rewards. For its practice in the Islamic banking of Al Qardh Al Hasan serves as a bailout fund for a short period of time, the customer will return it quickly, as a facility to obtain funds quickly because the customer cannot withdraw the funds, for example due to being stranded in deposits, as a facility to help small and medium businesses or social community. The benefits of aqad al-qardh are helping customers who need fast funds, as well as one of the giver characteristics between Islamic banks and conventional banks which contain social missions, in addition to commercial missions, improve good image and increase community loyalty to Islamic banks.